Comprehensive School Mental Health: An integrated “School-Based Pathway to Care” model for Canadian secondary schools - Wei, Yifeng; Kutcher, Stan; Szumilas, Magdalena (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2011)
Adolescence is a critical period for the promotion of mental health and the treatment of mental disorders. Schools are well-positioned to address adolescent mental health. This paper describes a school mental health model, “School-based Pathway to Care,” for Canadian secondary schools that links schools to primary care providers, mental health services, and the wider community, enabling them to address youth mental health in a collaborative manner. The model highlights the fundamental role of mental health literacy, gatekeeper training, and education/health system integration in improving adolescent mental health, and enhancing learning environments and academic outcomes.